Pharmacogenomics-Guided Antidepressant Therapy as a Solution to Treatment-Resistant Depression: A Systematic Review - Leah Rose Alexander (BJPsych Open, 2025)
Aims: Treatment-resistant depression (TRD), defined as failure to achieve remission despite adequate antidepressant trials, remains a pervasive clinical conundrum, linked to reduced quality of life, increased mortality, and higher healthcare costs. Pharmacogenomics-guided treatment (PGT) offers a potential solution to the ongoing challenge of TRD by using genomic testing to identify genetic factors influencing drug metabolism and response. This systematic review aimed to assess whether PGT improves symptom remission in adults with TRD compared with treatment as usual (TAU). Secondary objectives included evaluating the impact of PGT on treatment response and overall symptom improvement.